LEARNING VOCABULARY: WHAT STRATEGIES ARE UTILIZED BY PRIMARY SCHOOL STUDENTS? - Nilam Wahyu Safira; Rusiana Rusiana (Universitas Muria Kudus, 2021)
The objectives of the study are to figure out the strategies and problems in learning vocabulary of the fifth grade students of SD 7 Cendono Dawe Kudus in academic year 2019/2020. This present study is a descriptive study which employed questionnaire and interview guideline in collecting the data. The participants were 20 students, 11 boys and 9 girls of fifth graders of SD 7 Cendono Dawe Kudus. The results revealed that the learning strategies utilized by the students in learning vocabulary are metacognitive strategy (21.45), memory strategy (18.95), compensation strategy (15.47), social strategy (14.96), cognitive strategy (14.71) and affective strategy (14.46). While the most problems faced by the students are spelling, pronunciation, memorizing, and meaning.